The integrated marketing communication in digital environment: a case study of local radio in Yogyakarta - Maulidina Atikah Rachmawati; Subhan Afifi (The Indonesian Journal of Communication Studies, 2021)
The internet and the digitization of media have expanded the ability of mass media to reach the public. Radio is one type of mass media that has developed by utilizing digital technology in the internet era. The development of new technology has expanded radio's ability to reach audiences. The utilization of various innovations through the internet has increased the role of interactive social communication of a radio station. Digitalization has made radio survive during intense competition from multiple types of media in the era of disruption. It is interesting to see how the radio station's integrated marketing communication strategy in the digital environment is changing. This study aims to determine local radio's integrated marketing communication strategy in Yogyakarta in a changing digital environment. This research uses a case study method with in-depth interviews and observation data collection techniques. The results show that radio marketing communication strategies still use various promotional tools with digital technology modifications in a changing digital environment. The case study of Swaragama FM Radio shows that this radio implements an integrated marketing communication strategy which consists of several strategies, namely: (1) Formulating Segmentation, Targeting, and Positioning by adjusting the radio marketing mix character (2) Integrating Advertising and Direct Marketing, (3) Optimizing Sales Promotion and Personal Selling, (4) Strengthening Branding through Public Relations, and (5) Building interaction with the audience through Social Media Marketing.